Total Knee Arthroplasty After High Tibial Osteotomy: No Differences Between Medial and Lateral Osteotomy Approaches - Preston, Stephen (Springer US, 2013)
BACKGROUND: High tibial osteotomy (HTO) has long been accepted as an effective treatment for unicompartmental osteoarthritis of the knee in young, active adults. For varus knees, the two most commonly performed valgus-producing HTOs are the lateral closing wedge and the medial opening wedge. Regardless of technique, some HTOs fail and are converted to TKA. To our knowledge, no studies have directly compared TKAs done after lateral closing-wedge osteotomies to those done after medial opening-wedge osteotomies. QUESTIONS/PURPOSES: We compared pain- and function-related outcomes and survivorship of TKAs in patients who previously underwent medial opening-wedge and lateral closing-wedge HTOs. METHODS: We reviewed our institutional database to identify all patients having undergone a HTO with subsequent conversion to TKA and identified 188 lateral closing-wedge HTOs and 77 medial opening-wedge HTOs. Mean followup was 88 months (range, 3–264 months) for the lateral closing-wedge HTO cohort and 59 months (range, 3–180 months) for the medial opening-wedge cohort. SF-12, WOMAC, and Knee Society Scores, as well as survivorship at 5 years, were compared between the two groups. Statistical analysis was completed using the independent-samples t-test. RESULTS: No differences were found between groups in postoperative SF-12 scores (p = 0.77 for the mental component summary score and p = 0.21 for the physical component summary score), WOMAC scores (p = 0.67), or Knee Society Scores (p = 0.80). No difference was found in survivorship between groups at 5 years. CONCLUSIONS: Our results suggest there is no difference in functional outcomes or survivorship of TKA in patients having previously undergone medial opening-wedge and lateral closing-wedge HTOs. LEVEL OF EVIDENCE: Level III, therapeutic study. See Instructions for Authors for a complete description of levels of evidence.